Peran Budaya Sekolah dalam Menciptakan Perubahan Pendidikan di SD Islam Al Ghaffar - Kunti Futhnaa Rozaanaa Maulida; Hasya Ramadhani; Moh. Ma’mun; Muhammad Wildan Habibi; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
School culture is one of the key factors influencing the quality of education in an institution. This study aims to describe the role of school culture in bringing about educational change at Al Ghaffar Islamic Elementary School. The study employs a qualitative approach using observation and interviews. The results of the study indicate that SD Islam Al Ghaffar implements a school culture rooted in the Qur’an and moral values, manifested through daily religious practices such as mandatory morning recitation sessions, the recitation of the Asmaul Husna, collective istighfar, and qira’ah as the school’s distinctive feature. Additionally, the school has developed the Al Ghaffar Method as an internal approach to Quranic education, which has been adopted by 18 schools in the Malang region. A culture of discipline is enforced through a tiered intervention system involving homeroom teachers, the student affairs office, and the principal. The involvement of all stakeholder teachers, students, parents, and the community is key to the successful implementation of the school culture. These findings demonstrate that a consistent and structured school culture can foster sustainable educational change, shaping students into individuals who are religious, disciplined, and of noble character.